Sequence variations in the ETEC CS6 operon affect transcript and protein expression. Issue 1 (1st January 2021) - Moon, Jonathan; Barry, Eileen M.
ABSTRACT: Enterotoxigenic Escherichia coli (ETEC) is a leading cause of diarrheal disease in developing nations where it accounts for a significant disease burden in children between the ages of 0 to 59 months. It is also the number one bacterial causative agent of traveler's diarrhea. ETEC infects hosts through the fecal-oral route and utilizes colonization factors (CF) to adhere within the small intestine. Over 25 CFs have been identified; 7 are considered major CFs and a vaccine targeting these is predicted to provide protection against up to 66% of ETEC associated disease. Coli Surface Antigen 6 (CS6) is a major CF and is associated with disease-causing ETEC isolates. Analysis of the CS6 operon sequence led to the identification of two regions of variability among clinical isolates which we predicted exert effects on CS6 transcript and protein expression. A total of 7 recombinant E. coli strains were engineered to encode the CS6 operon in wild-type, hybrid, and mutant configurations. Western blot analysis and RT-qPCR provided evidence to support the importance of an intergenic hairpin structure on CS6 expression. Our results reveal the significance of CS6 sequence selection regarding ETEC vaccine development and present novel information regarding CS6 sequence variation in WT ETEC strains.